2020
DOI: 10.1002/anie.202004377
|View full text |Cite
|
Sign up to set email alerts
|

A Heteroleptic Dirhodium Catalyst for Asymmetric Cyclopropanation with α‐Stannyl α‐Diazoacetate. “Stereoretentive” Stille Coupling with Formation of Chiral Quarternary Carbon Centers

Abstract: The heteroleptic dirhodium paddlewheel catalyst 7 with achiral carboxylate/acetamidate ligand sphere is uniquely effective in asymmetric [2+ +1] cycloadditions with a-diazo-atrimethylstannyl (silyl, germyl) acetate.O riginally discovered as at race impurity in as ample of the homoleptic parent complex [Rh 2 ((R)-TPCP) 4 ](5), it is shown that the protic acetamidate ligand is quintessential for rendering 7 highly enantioselective.The-NH group is thought to lock the ensuing metal carbene in place via interligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 93 publications
(21 reference statements)
0
26
0
Order By: Relevance
“…This finding has implications for catalysis, as a chiral relative of 16 was recently shown to be uniquely effective in asymmetric cyclopropanation reactions of α-stannyl(silyl) α-diazoesters. 49 Indirect evidence suggested that these reactions proceed at the rhodium face carrying the protic −NH group, which according to the shift data is the (much) less electrophilic site; this conclusion clearly mandates further scrutiny. In any case, 103 Rh NMR makes it unambiguously clear that carboxylate- and carboxamidate-based paddlewheel complexes are very distinct types of catalysts in electronic terms.…”
mentioning
confidence: 99%
“…This finding has implications for catalysis, as a chiral relative of 16 was recently shown to be uniquely effective in asymmetric cyclopropanation reactions of α-stannyl(silyl) α-diazoesters. 49 Indirect evidence suggested that these reactions proceed at the rhodium face carrying the protic −NH group, which according to the shift data is the (much) less electrophilic site; this conclusion clearly mandates further scrutiny. In any case, 103 Rh NMR makes it unambiguously clear that carboxylate- and carboxamidate-based paddlewheel complexes are very distinct types of catalysts in electronic terms.…”
mentioning
confidence: 99%
“…3a , b as the parent complexes of this series excel in cyclopropanation, cyclopropenation, and certain insertion reactions; as many variations of the conceptually new design can be envisaged, one may have high expectations for future generations of catalysts of this type. Opportunities along these and related lines 99 , 100 are actively pursued in our laboratory.…”
mentioning
confidence: 99%
“…Future work must hence try to gain deeper understanding for and better control over this particular parameter. For our long‐standing interest in various aspects of metal carbene chemistry in general, [41–49] we are committed to doing so; encouraging lead findings along these lines have recently been disclosed [50]…”
Section: Discussionmentioning
confidence: 99%